The impact of intraoperative mapping during re-resection in recurrent gliomas: a systematic review - Opijnen, Mark van; Sadigh, Yasmin; Dijkstra, Miles E.; Young, Jacob S.; Krieg, Sandro; Ille, Sebastian; Sanai, Nader; Rincon-Torroella, Jordina; Maruyama, Takashi; Schucht, Philippe; Smith, Timothy R.; Nahed, Brian V.; et al. (Journal of neuro-oncology, 2025)
Purpose: Previous evidence suggests that glioma re-resection can be effective in improving clinical outcomes. Furthermore, the use of mapping techniques during surgery has proven beneficial for newly diagnosed glioma patients. However, the effects of these mapping techniques during re-resection are not clear. This systematic review aimed to assess the evidence of using these techniques for recurrent glioma patients. Methods: A systematic search was performed to identify relevant studies. Articles were eligible if they included adult patients with recurrent gliomas (WHO grade 2–4) who underwent re-resection. Study characteristics, application of mapping, and surgical outcome data on survival, patient functioning, and complications were extracted. Results: The literature strategy identified 6372 articles, of which 125 were screened for eligibility. After full-text evaluation, 58 articles were included in this review, comprising 5311 patients with re-resection for glioma. Of these articles, 17% (10/58) reported the use of awake or asleep intraoperative mapping techniques during re-resection. Mapping was applied in 5% (280/5311) of all patients, and awake craniotomy was used in 3% (142/5311) of the patients. Conclusion: Mapping techniques can be used during re-resection, with some evidence that it is useful to improve clinical outcomes. However, there is a lack of high-quality support in the literature for using these techniques. The low number of studies reporting mapping techniques may, next to publication bias, reflect limited application in the recurrent setting. We advocate for future studies to determine their utility in reducing morbidity and increasing extent of resection, similar to their benefits in the primary setting.